2015
DOI: 10.1136/bmj.h6246
|View full text |Cite
|
Sign up to set email alerts
|

Length of hospital stay after hip fracture and risk of early mortality after discharge in New York state: retrospective cohort study

Abstract: Study question Can the length of hospital stay for hip fracture affect a patient's risk of death 30 days after discharge?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 17 publications
9
98
2
3
Order By: Relevance
“…The Nikkel et al result conflicted with two European studies that found longer LOS were associated with decreased risk of mortality [31,32]. Nikkel et al (2015) argue that the contradiction could be due to differences in treatment structures (e.g., time management of hip fracture treatments) or payment systems (e.g. financial considerations in the U.S. that might yield a more rapid discharge), concluding that caution should be used when comparing results from different health care systems [33].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The Nikkel et al result conflicted with two European studies that found longer LOS were associated with decreased risk of mortality [31,32]. Nikkel et al (2015) argue that the contradiction could be due to differences in treatment structures (e.g., time management of hip fracture treatments) or payment systems (e.g. financial considerations in the U.S. that might yield a more rapid discharge), concluding that caution should be used when comparing results from different health care systems [33].…”
Section: Discussionmentioning
confidence: 96%
“…The estimated LOS differences between SNH and NSNH may result in poorer health outcomes for hip fracture patients treated at SNH relative to those treated at NSNH. Nikkel et al [33], using a sample of 169,258 patients from the New York State SPARCS dataset, found that shorter LOS for hip fracture treatments was associated with reduced rates of mortality. The Nikkel et al result conflicted with two European studies that found longer LOS were associated with decreased risk of mortality [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations